Dampak Penerapan Perubahan Tarif PPN Menurut UU HPP No. 7 Tahun 2021 pada PT. POV - Alya Safira, Miya; Sunani, Avi (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2024)
Tax regulations in Indonesia have undergone many changes by harmonizing tax regulations with the hope of increasing stable and balanced economic growth and recovery after covid-19 by increasing the VAT rate to 11% as regulated in the HP law number 7 of 2021.The purpose of this study is to determine the possible impact on PT POV related to the change in Value Added Tax rate. The qualitative method is the method that has been applied to conduct this research, which uses a descriptive approach by explaining a phenomenon that occurs and describing events in the field. Data collection techniques are obtained through interviews and documentation. The results of this study indicate that changes in the amount of VAT rates cause adjustments to the system by KJA in managing VAT at PT POV, namely related to e-invoicing and Microsoft Excel applications. Changes in VAT rates also affect sales made by PT POV which have decreased significantly from the March 2022 tax period before the tax rate has changed to 11%. Researchers provide advice to future researchers to conduct research with a wider object related to the impact of changes in VAT rates.